Application of Psychrotolerant Antarctic Bacteria and Their Metabolites as Efficient Plant Growth Promoting Agents - Styczynski, Michal; Biegniewski, Gabriel; Decewicz, Przemyslaw; Rewerski, Bartosz; Debiec-Andrzejewska, Klaudia; Dziewit, Lukasz (Frontiers in Bioengineering and Biotechnology, 2022)
Iron is the fourth most abundant element on earth. However, its low bioavailability is a key plant-growth limiting factor. Bacteria play an important role in plant growth promotion since they produce specific secondary metabolites that may increase macro- and micronutrient accessibility in soil. Therefore, bacterial-derived iron chelators, as well as surface-active compounds, are recognised as essential to plant welfare. In this study, three cold-active Antarctic bacterial strains, i.e. Pseudomonas sp. ANT_H12B, Psychrobacter sp. ANT_H59 and Bacillus sp. ANT_WA51, were analysed. The physiological and genomic characterisation of these strains revealed their potential for plant growth promotion, reflected in the production of various biomolecules, including biosurfactants (that may lower the medium surface tension of even up to 53%) and siderophores (including ANT_H12B-produced mixed-type siderophore that demonstrated the highest production, reaching the concentration of up to 1.065 mM), increasing the availability of nutrients in the environment and neutralising fungal pathogens. Tested bacteria demonstrated an ability to promote the growth of a model plant, alfalfa, increasing shoots’ length and fresh biomass even up to 26 and 46% respectively; while their metabolites increased the bioavailability of iron in soil up to 40%. It was also revealed that the introduced strains did not disrupt physicochemical conditions and indigenous soil microbial composition, which suggests that they are promising amendments preserving the natural biodiversity of soil and increasing its fertility.